АСПЕКТИ ПРАКТИЧНОЇ ПІДГОТОВКИ ФАХІВЦІВ З ФІЗИЧНОЇ ТЕРАПІЇ РІВНЯ «БАКАЛАВР» У ЧЕРНІВЕЦЬКОМУ НАЦІОНАЛЬНОМУ УНІВЕРСИТЕТІ ІМЕНІ ЮРІЯ ФЕДЬКОВИЧА - Kozik, Nataliia Mykolaiivna; Stratiichuk, Nataliia Anatoliivna; Lohuch, Lesia Hennadiivna; Kukovska, Iryna Lubomyrivna; Stefanchuk, Vasyl ivanovych (Вісник Прикарпатського університету. Фізична культура. ДВНЗ Прикарпатський національний університет імені Василя Стефаника, 2019)
The article dwells on the ways of improving practical training of physical therapy specialists studying to gain Bachelor’s degree at Chernivtsi National Yurii Fedkovych University. The objective of this work is to study how certain methodologies influence practical skills of the future physical therapists during the clinical neurological practice. In the process of work, such research methods as observation, polls, performance analysis and mathematical processing of data were used. The case study was conducted at the clinical bases of neurological practice in the city of Chernivtsi involving the students of the 4th year of full-time and part-time study. In order to consolidate theoretical knowledge, individual rehab programs for given neurological diagnoses were developed. Diagnostic skills were optimized using methodological recommendations regarding the order of examinations and ways of result interpretation. The development of rehabilitation complexes and analysis of prescribed treatment contributed to improved understanding of the tasks performed. This study proved that the proposed methodological techniques increase the efficiency of theoretical knowledge consolidation and improve practical skills of students. Conclusion: Clinical neurological practice enables physical therapy students to improve their theoretical and practical training for the future professional activities. The use of clear methodological recommendations and development of practical skills allow students to meet the requirements of the Standards of Higher Education of Ukraine for gaining Bachelor’s degree in "Physical therapy, ergotherapy". Стаття присвячена вдосконаленню практичної підготовки фахівців з фізичної терапії освітньо-кваліфікаційного рівня «бакалавр» у ЧНУ ім. Ю. Федьковича. Метою дослідження було вивчення впливу певних методичних засобів на якість навичок та умінь у майбутніх фізичних терапевтів під час проходження клінічної неврологічної практики. В роботі використовувались такі методи дослідження як спостереження, анкетування, аналіз успішності та математичної обробки отриманих даних. В результаті експерименту, проведеного на клінічних базах неврологічної практики м. Чернівці зі студентами 4 курсу денної та заочної форми навчання, виявлено, що запропоновані педагогічні прийоми (використання методичних рекомендацій, зразків та схем неврологічного та фізіотерапевтичного обстеження, розробка практикантами індивідуальних реабілітаційних програм) та проведення захисту практики із демонстрацією практичних навичок підвищують ефективність засвоєння теоретичних знань та вдосконалюють уміння майбутніх фахівців з фізичної терапії.
PHYSICAL THERAPY PROFESSIONALS STUDYING FOR THE BACHELOR’S DEGREE AT CHERNIVTSI NATIONAL YURII FEDKOVYCH UNIVERSITY.
Keywords: physical therapy, clinical practice, Bachelor’s degree, higher education, individual rehabilitation program, practical skills, diagnostics, physiotherapeutic intervention